Association between Physical Activity Level and Health-Related Quality of Life of Children With and Without Epilepsy - Ogwumike, Omoyemi Olubunmi; Agboke, Monsurat Afolake; Adeniyi, Ade Fatai (Journal of Pediatric Neurology, 2016)
Physical activity (PA) appears to be limited in children with epilepsy (CWE). The unpredictability of seizure recurrence results in overprotection, isolation, and needless restrictions in their activity. PA level and health-related quality of life (HRQoL) of CWE and children with no epilepsy (CWNE) were investigated. Data were analyzed using chi-square test and Spearman rank correlation coefficient. Majority reported moderate PA level, with a significantly lower mean PA score (2.45 ± 0.68) in CWE compared with CWNE (3.06 ± 0.72). Significant positive correlation was observed between HRQoL and PA level. However, CWE scored lower on every HRQoL scale item when compared with CWNE. It is imperative for CWE to be physically active to improve their HRQoL.
Keywords: children with epilepsy; health-related quality of life; physical activity